2017
DOI: 10.3390/toxins9090264
|View full text |Cite
|
Sign up to set email alerts
|

Sinapic Acid Affects Phenolic and Trichothecene Profiles of F. culmorum and F. graminearum Sensu Stricto

Abstract: Plant-derived compounds for reducing the mycotoxin load in food and feed have become a rapidly developing research field of importance for plant breeding efforts and in the search for natural fungicides. In this study, toxigenic strains of Fusarium culmorum and F. graminearum sensu stricto were exposed to sinapic acid on solid YES media at levels close to those reported in wheat bran. Fusaria produced phenolic acids, whose accumulation was decreased by exogenous sinapic acid. Strains exposed to the lowest dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
(72 reference statements)
2
18
0
Order By: Relevance
“…In this study, it was found for the first time that flavonoids display variable effect on fungal secondary metabolic profiles. The observed high variability is in line with previous reports demonstrating variable effects of other plant resistance related compounds such as phenolic acids [ 44 , 45 ] and lignans [ 60 ] on this group of toxigenic fungi. Notably, the in vitro results presented in this paper are in line with recent in planta studies demonstrating that resistance to Fusarium diseases is closely associated with the promoted biosynthesis of phenylpropanoids, including flavonoids [ 33 , 43 , 61 , 62 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, it was found for the first time that flavonoids display variable effect on fungal secondary metabolic profiles. The observed high variability is in line with previous reports demonstrating variable effects of other plant resistance related compounds such as phenolic acids [ 44 , 45 ] and lignans [ 60 ] on this group of toxigenic fungi. Notably, the in vitro results presented in this paper are in line with recent in planta studies demonstrating that resistance to Fusarium diseases is closely associated with the promoted biosynthesis of phenylpropanoids, including flavonoids [ 33 , 43 , 61 , 62 ].…”
Section: Resultssupporting
confidence: 91%
“…Previous in vitro studies showed that different strains of F. culmorum and F. graminearum s.s. accumulate phenolic acids in the media [ 44 , 45 ]. In this study, we screened fungi for flavonoid production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study, this effect was only observed for FP, but not for FG and FL. This indicates that FP is not as sensitive to p-hydroxybenzoic acid as FG and FL which could be due to a transformation of the acid into a less affecting substance, as observed by Kulik et al (2017). Also, a potential interference with trichothecene biosynthesis at the transcriptional level (Pani et al 2016) which occurs in FG and FL, but not in FP, should be investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Sinapic acid have been shown to affect the production of trichothecenes by F. culmorum and F. graminearum, which also respond by stimulation of ergosterol. This effect might be indirect since treatment with sinapic acid led to dramatic accumulation of its biosynthetic precursor ferulic acid, and chlorogenic acid biosynthesis [59]. Both compounds have caffeic acid as a common precursor, and an increased accumulation of caffeic acid may occur in the early incubation period of fungi in the presence of sinapic acid [59].…”
Section: Discussionmentioning
confidence: 99%